Financial structure of public enterprises - "Bhargava, N.K." (Jaipur, 1991)
In the post independence era, the public sector came into being and assigned specific role of putting economy on sound footings and providing Social Justice to common man. The perfor mance of any undertaking, at last, is judged through its success or failure in monetary terms. This issue assumes great importance in the case of a deve loping economy in view of its financial constraints and scarce skill of utilising them to the maximum. Here comes up the question of examining financial structure. This study deals with all the aspects of financial structure of public sector undertakings in a developing economy, examines them critically and offers concrete suggestions which may prove of great value to the authorities involved in managing financial affairs of such undertakings.
Keywords: Government business enterprises Finance